Complications Related to Sexualized Drug Use: What Can We Learn From Literature? - Donnadieu-Rigole, Hélène; Peyrière, Hélène; Benyamina, Amine; Karila, Laurent (Frontiers in Neuroscience, 2020)
Chemsex is described as the use of specific psychoactive substances during sexual activity to sustain, enhance, disinhibit or facilitate the sexual experience. It preferentially concerns men who have sex with men. They use new synthetic substances like cathinones, methamphetamines, GBL/GHB, ketamine and cocaine. The prevalence of ChemSex varies from 3 to 31% during lifetime. The Internet has participated significantly in the evolution of sexual behaviors, both in terms of sexual dating and the availability of new synthetic substances. The advent of geolocation applications contributed to the development of chemsex. The literature describes many complications linked to these sexual practices; the main clinical effects related to cathinones consumption were psychiatric symptoms; agitation, hallucinations, anxiety, suicidal ideation, paranoia, and confusion. Regular GBL/GHB consumption alter cognitive functions, particularly memory and emotion management. Use of these drugs in party and play is dramatically associated with high-risk sexual behaviors. The prevalence of hepatitis B, hepatitis C syphilis and HIV is higher in men who use methamphetamine and Viagra and/or who declared they practiced slamming, chemsex, and fisting. Other STIs such as gonorrhea have increased with methamphetamine and GHB/GBL use. Actually, the care of individuals who practice Chemsex in a problematic way is currently not codified, but the use of integrative and specific interventions is necessary.